Numerical study of a SiC mould subjected to a spark plasma sintering process. (February 2015) - Byon, Chan; Li, Ming-Han; Kakegawa, Kazuyuki; Han, Young-Hwan; Lee, Dong-Yeon
Abstract : Spark plasma sintering (SPS) is a material processing technique based on the Joule heating of a mould and powder under an electrical pulse or DC current. This study demonstrates the use of silicon carbide (SiC). A finite-element numerical study was performed to predict the temperature and stress distributions during SPS. In addition, it was found experimentally that SPS using SiC exhibits similar behaviour to that with a conventional graphite die.